Sosialisasi dan Pelatihan Digitalisasi Informasi Desa Melalui Website PRODIGDES di Desa Botutonuo - Lillyan Hadjaratie; Indhitya R Padiku; Alfian Zakaria; Eka Vickraien Dangkua; Rizqi Firmansya Tamimu; Muhammad Khairul Azhari Ali; Nurkesya Nurkesya; Mohammad Safwan Ahmad (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2026)
Conventional and paper-based data management in rural areas often leads to suboptimal public transparency and slow dissemination of regional potential. This Impact KKN program aims to empower village officials in transforming data governance through the self-managed Village Digital Profile (PRODIGDES) website in Botutonuo Village, Bone Bolango Regency. The implementation employs a participatory empowerment approach, including village consultations, collaborative data collection, intensive one-on-one mentoring, and partner independence evaluation. This program successfully converted analog monograph data into a centralized digital portal featuring demographic infographics, APBDes budget transparency, social assistance distribution, and visualization of marine tourism and local MSMEs. Evaluation results show a notable improvement in digital literacy capacity, as village officials are now able to independently update and manage content without student supervision. This platform effectively stimulates public trust while mitigating the risk of a "zombie website." In conclusion, PRODIGDES has successfully achieved the target of sustainable village data management modernization.